Low-concentration dual-baricity thoracic segmental spinal anesthesia for laparoscopic cholecystectomy: a retrospective case series - Paolo Scimia; Massimiliano Luca D'Agostino; Antonio De Cato; Franco Marinangeli; Simone Cicconi; Riccardo Moretti; Federica Venturoni; Fabrizio Fattorini; Roberto Starnari; Domenico Pietro Santonastaso; Luca Gentili (Advances in Anesthesia and Pain Medicine, 2026)
Laparoscopic cholecystectomy (LC) is usually performed under general anesthesia (GA), which provides airway protection and optimal surgical conditions but may expose vulnerable patients to cardiopulmonary stress and other anesthesia-related adverse effects. Thoracic segmental spinal anesthesia (TSSA) may represent an alternative in selected patients. We evaluated the feasibility, safety, and perioperative outcomes of a low-concentration dual-baricity TSSA protocol for LC. This retrospective descriptive case series included 26 consecutive patients undergoing LC between February 2025 and February 2026. Spinal anesthesia was performed at T9-T10 using 2 mL of hypobaric ropivacaine 0.25%, followed by 4 mL of isobaric ropivacaine 0.25% (total dose 15 mg), without intrathecal adjuvants. Sedation was achieved with intravenous dexmedetomidine, midazolam, and fentanyl. Intraoperative adverse events, postoperative pain, motor block, analgesic requirements, recovery quality, and patient satisfaction were recorded. All procedures were completed under TSSA without conversion to GA. One patient required conversion from laparoscopic to open cholecystectomy, with no change in anesthetic technique. No intraoperative abdominal pain, hypotension, nausea, or vomiting occurred; shoulder pain was reported in 11.54% of patients. Postoperative nausea and vomiting occurred in 3.85%. Mean Bromage score was 0.03±0.19. Mean Visual Analog Scale (VAS) scores were 0±0 at 0 hours, 1.8±2.05 at 12 hours, and 0.73±1.66 at 24 hours. Mean Quality of Recovery-15 questionnaire (QoR-15) score was 145.96±3.15, and all patients reported the highest satisfaction score. Low-concentration dual-baricity TSSA provided effective surgical anesthesia with preserved spontaneous ventilation, stable hemodynamics, minimal motor blockade, low postoperative pain, and high patient satisfaction. This technique may represent a feasible alternative to GA in appropriately selected patients.